Religious Identity, Citizenship, and Welfare: The Case of Muslims in Britain (American Journal of Islam and Society, 1993)
In addressing the situation of Muslim communities in Britain, it isapparent that one of the major frameworks for understanding their situationhas been the notion of "Citizenship," for citizenship is a means ofidentifying critical aspects of the relationship between the individual andthe state. Following Bottomore (1992), we may make a useful distinctionbetween "formal" and "substantive" citizenship: the former being Simplydefined as "membemhip in a nation state" and the latter as "an array ofcivil, political, and especially social rights, involving also some kind ofparticipation in the business of government'' (ibid.).There are a number of salient points that should be made in relationto examining the implications of this distinction. First, we may note thatthe legal definition of citizenship is always informed by the cultural andethnic agendas historically rooted in the foundation myths of each nationstate.Thus in France, for example, just as the revolutionary iconographyof the Tricolor, Marianne, and Liberty, Equality, and Fratemity continueto serve contemporary national sentiments (Hobsbawm 1983), so todayFrench legal framing of formal citizenship is infused with its revolutionaryroots:La tradition centraliste francaise interdit la reconnaissance dansl'espace public des 'communautes', au sens oii elles existent auWtats-Unis. (Schnapper 1990).Consequently, in France neither ethnicity nor religion are formally relevantin determining access to citizenship ...